PENGARUH LABA, ARUS KAS, PERTUMBUHAN, DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Robert Jao (P3M STMIK Profesional Makassar, 2013)
Abstract The aims of the research are to find out (1) influence of net income on dividend payout ratio, (2) influence of cash flow on dividend payout ratio, (3) influence of growth on dividend payout ratio, (4) influence of size on dividend payout ratio. This study drew 34 samples from manufacturing companies listed in Indonesia Stock Exchange with a purposive sampling technique. The research data was collected from annual reports within a period 2009 to 2011 of the Capital Market Reference Centre of Indonesian Stock Exchange. The method of analysis was multiple linear regression.The results of the study indicated that (1) net income had significant negative influence on dividend payout ratio, (2) cash flow had no significant influence on dividend payout ratio, (3) growth had no significant influence on dividend payout ratio, (4) size had no significant influence on dividend payout ratio